LEGAL PROTECTION FOR PROFESSIONAL NURSES WORKING IN HOSPITAL HEMODIALYSIS ROOMS - Yus Baimbang Bilabora (Faculty of Law, Universitas Lampung, 2023)
Providing services in the hemodialysis room, doctors, nurses, and even hospitals must also be prepared to be responsible for all related activities. If nurses are required to take actions beyond their authority (collaborative actions), they must get protection for the risks they face. This study examines (1) the procedure for delegating authority from doctors to nurses in providing services in the hemodialysis room, (2) the responsibilities of nurses working in the hospital hemodialysis room, and (3) policies related to legal protection for the professional nurse working in the hospital hemodialysis room. The problem approach used in this research is a normative juridical approach. The normative juridical approach used in this thesis research is the statutory approach. In addition, the research uses secondary data consisting of primary, secondary, and tertiary legal materials. Based on the research results, the procedure for delegating authority from doctors to nurses to provide services in the first hemodialysis room has several stages. First, the implementing doctor must ensure that the authority given is written, the recipient of the authority has the required competence, the willingness of the recipient of authority, and the implementation of hemodialysis under the supervision of the implementing doctor. If the conditions have been met, the delegation of authority can be implemented. Based on the vocational skills and profession of the hemodialysis nurse, delegation of authority can occur on a mandate basis, with active supervision from the implementing doctor. If it is to the requirements for the delegation of authority, then hemodialysis is carried out by skilled nurses under the supervision of the implementing doctor. The responsibilities of a nurse working in a hospital hemodialysis room are regulated based on professional and legal provisions in Indonesia, namely criminal, civil, and administrative. There are several perspectives. Legal protection for nurses in the hemodialysis room is related to competence based on the Regulation of the Minister of Health (Permenkes) of the Republic of Indonesia concerning the Implementation of Dialysis Services in Health Facilities. However, the Standard Operating Procedures for the hemodialysis room are returned to each hospital’s policies.